2009
DOI: 10.1186/gb-2009-10-7-r79
|View full text |Cite
|
Sign up to set email alerts
|

Methods for analyzing deep sequencing expression data: constructing the human and mouse promoterome with deepCAGE data

Abstract: Deep sequencing expression analysis methods

A set of methods is presented for normalization, quantification of noise and co-expression analysis for gene expression studies using deep sequencing.

AbstractWith the advent of ultra high-throughput sequencing technologies, increasingly researchers are turning to deep sequencing for gene expression studies. Here we present a set of rigorous methods for normalization, quantification of noise, and co-expression analysis of deep sequencing data. Using these meth…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 28 publications
6
132
0
1
Order By: Relevance
“…PCR amplification and reverse transcription artifacts were found to be nonnegligible in both Balwierz et al (2009) Marioni et al (2008) found that variation across lanes generally follows a Poisson sampling process, they did observe considerably more variation for a nonnegligible number of genes (on the order of 10 2 ). Balanced blocks by multiplexing: To eliminate confounding caused by batch or lane effects, consider the situation in which all samples of RNA are pooled into the same batch and then sequenced in one lane of a flow cell.…”
Section: Balanced Block Designsmentioning
confidence: 99%
“…PCR amplification and reverse transcription artifacts were found to be nonnegligible in both Balwierz et al (2009) Marioni et al (2008) found that variation across lanes generally follows a Poisson sampling process, they did observe considerably more variation for a nonnegligible number of genes (on the order of 10 2 ). Balanced blocks by multiplexing: To eliminate confounding caused by batch or lane effects, consider the situation in which all samples of RNA are pooled into the same batch and then sequenced in one lane of a flow cell.…”
Section: Balanced Block Designsmentioning
confidence: 99%
“…The abundance of CAGE tags that map to a putative promoter region provides quantitative measurement of the extent of transcription initiation at that site; this is capable of estimating expression of the associated genes (Balwierz et al 2009;Murata et al 2014). In this way, we sought to identify promoters with differential activity, differentially-expressed genes across the three states surveyed by our CAGE experiment.…”
Section: Differential Activity Of D Pulex Promotersmentioning
confidence: 99%
“…To account for this, we modeled the stranded signal throughout genes as a mixture of signal originating from promoter regions and background. We modeled the background as a mixture of signal linearly proportional to transcript expression level as measured by stranded RNA-seq of total RNA (Methods) and uniform unstranded signal, which we treated as random noise in a manner similar to Balwierz et al (2009). All CAGE tags that could be explained by our model as RNA background or random noise (18% of mapped tags) were removed from subsequent analysis (Supplemental Methods), resulting in a set of 21 million filtered aligned CAGE tags.…”
Section: Massively Parallel Mapping Of Tsss In the Drosophila Embryo mentioning
confidence: 99%